Comparison Infection Rate between Inside-Out and Outside-In Tunneling of External Ventricular Drains - Hansasuta, Ake; Sangkarin, Kobkit (Thai Journal of Neurological Surgery, 2025)
Background: An external ventricular drain (EVD) is a valuable procedure in the management of temporary cerebrospinal fluid (CSF) diversion. It is associated with the well-known risk of CSF infection (range, 0% to 27%). But there has been no study which determines EVD related infections between different techniques of tunneling (inside-out vs. outside-in). In theory, we believe that the inside out tunneling reduce the infection by the fact that it does not introduce cutaneous pathogens into the ventricles. Objective: To compare the infection rates between the different techniques of inside-out and outside-in tunneling of EVD. Methods: All patients requiring EVD system in Ramathibodi hospital from August 2009 to August 2013 were enrolled. The outside-in group was retrospectively reviewed and prospective data collection was performed in the inside-out group.The evidence of CSF infection prior to the procedure, including meningitis, infected implant (shunt system), or ventriculitis were excluded. CSF samples for culture were collected at the time of EVD insertion and removal. For each patient we record age, sex, diagnosis, GCS at presentation, co morbidity, systemic infection, steroid use, operative time, tunnel length, position of bur hole, duration of EVD in situ, EVD access and cultured organism. Results: 234 EVDs in 170 patients were included in the study. There were 12 CSF infection noted, 6 of 113 (5.3%) in the inside-out group and 6 of 121 (4.9%) in the outside-in. The infection rate was not significantly different (P=0.93). Previous EVD insertion was found to increase the infection rate(P=0.01) but gender, GCS, systemic infection, co morbidity, position of EVD, operating time, steroid usage, duration of EVD, SAH and IVH were not correlated. Conclusions: The infection rates of inside-out and outside in tunneling of EVD were similar. Among various factors, only previous EVD insertion was found to increase infection rate.